Basic model for information retrieval based on free-text in database application - Omar, Mohd Adan; Mat Cha, Md Zahir; Idrus, Mohd Rushdi (2009)
The purpose of this article is to design the basic model for information retrieval based on free-text domain in a particular database environment. It is an alternative method to the usage of key that is widely used in today database applications. At the end of this paper, we show the prototype that has been developed to support the freetext model verification. The result from the testing process is also given.